MODOS DE RECONCILIACIÓN. DOS REMAKES DE FILMES DE LOS SESENTA EN EL CINE ARGENTINO CONTEMPORÁNEO - Dr. Jorge SALA (Fonseca, Journal of Communication, 2023)
The article analyzes two contemporary movie remakes of the 60s cinemas in Argentina: Aniceto (Leonardo Favio, 2008) and La patota (Santiago Mitre, 2015). The objective is to explore the transformations and continuities between the source texts and the later subsidiary texts. It tries to recognize the immanent issues, the procedural and pragmatic aspects involved in these rewriting operations.